Controller Placement and Availability Link Upgrade Problem in SDN Networks - Santos, Dorabella (2020)
In SDN networks, the problem of how many controllers and where to place them, has been extensively studied. This is known as the controller placement problem, and has been addressed mainly considering the delays between the SDN switches and controllers. Although the delays between switches and controllers and the intercontroller delays are key aspects, a less addressed issue is the availability of the control paths (the routing paths between the switches and their controllers). In this paper, the problem regarding controller placements with QoS requirements, both in terms of delays and availability of the control paths, is addressed. To guarantee the availability requirements, a set of links is selected to have upgraded availability. An exact method and a heuristic method are proposed for solving the problem. Computational results show that the heuristic method provides near-optimal solutions within reasonable runtimes, when the exact method becomes computationally expensive.